Control de oxidación en camarón litopenaeus vannamei utilizando baños de solución de ácido cítrico - González Blacio, Dalton Isaac (2012)
One of the main problems in the preservation of perishable shrimp is the degradation of fats, to investigate which would be the results of the implementation of toilets with solutions of citric acid in the muscle of shrimp. Lipids are a group of organic molecules, most biomolecules, composed primarily of carbon and hydrogen. Lipids suffer chemical deterioration resulting from oxidation, often referred to as rancidity, this is a major cause of the loss of food quality. The most common type of fat is one in which three fatty acids are attached to the glycerol molecule. The n-3 fatty acids are found mainly in marine products. Ascorbic acid or vitamin C is an antioxidant monosaccharide found in animals and plants. Since it can not be synthesized by humans and must be obtained from the diet is a vitamin. Sorbates are very toxic, the least of all the preservatives, for this reason its use is allowed throughout the world. And is used as an antioxidant in our research that it took place in the shrimp processing plant Marest Brand and Processing Laboratory of Aquatic Organisms, for which we propose the following objective: To evaluate the oxidation that occurs in the Litopenaeus vannamei shrimp muscle baths using citric acid solutions. The results we obtained were that the concentration of acid than it should be applied to 1% so that no changes in the texture of the raw material, with positive results within the limits suitable for human consumption.